SOCIAL STRATIFICATION AMONG THE URBANIZED FISHING COMMUNITIES IN CITY OF MAKASSAR - Sudarmono Sudarmono (Sosiohumaniora, 2023)
Fishing activities along the coastal areas of Makassar City are influenced by the type of technology used and also the social structures of production process that involved key players, such as wholesalers, exporters, and small-scale fishermen. This article aims (1) to explain the trajectory of fishing development of Makassar City and its impact to the creation of social stratification and (2) to analyze the economic factors that influenced the decision-making processes among producers, especially related to its impact towards small-scale fishermen. Data and information were obtained based on interview and field observation that had been conducted in three fishing communities in the City of Makassar, between September 2019 and January 2020. It is found that globalization impacted the issue of underdevelopment of the small-scale production among poor fishermen; which also indicates the powerlessness concerning the possession of high capacity harvesting equipment commonly owned by the capitalist producers. Social stratifications that were formed among fishermen had placed the small-scale fishermen at the lower level, while the middlemen who have control over capital also have access to the marketing networks and opportunities, thus placing their position at a higher level.